Inventory control analysis using economic order quantity with discount factor - Annisa Wahyuni; Gesit Thabrani (Operations Management and Information System Studies, 2021)
This study aims to calculate the stock determination and arrange the stock size using the economic order quantity (EOQ) technique with the discont factor at PT. Primajaya Maju Bersama Padang and calculate the minimum cost of shares using a different EOQ procedure. This exam is a graphic exploration (enlightenment). Important information is gathered through perceptions, meetings and writing audits. Requesting information from the last three years is used to estimate interest by applying the linear trend technique, winter strategy, and exponential smoothing. In addition, anticipated demand information will be used to plan merchandise requirements with EOQ. The consequence of this investigation shows that the exponential smoothing strategy is the best technique to use in anticipating demand in 2020. The exponential smoothing technique is used to ensure the least cost of stock and costs. With the economic order quantity (EOQ) method with discount factor, the total cost is 240,818,176 IDR.